PERAN HUKUM KRIMINOLOGI DALAM UPAYA MEMBANTU HUKUM PIDANA - Nurul Aulia (PT. Habe Cendekia Utama, 2025)
Criminal law and criminology complement each other, with criminology focusing on the reasons that drive crime and legal consequences, and criminal law connecting criminal acts to evidence. In crime, rational choice theory is used as a shortcut if a person's most important desires fail to be achieved, emphasizing actors and resources. Heri Kurniawan, an actor, chose to commit crime as a survival strategy, choosing rational crime. Criminology defines crime as deviant behavior, a social phenomenon carried out by a person or group consciously. Heri, who committed robbery and murder, was charged under Article 365 of the Criminal Code concerning theft with violence and Article 338 of the Criminal Code concerning murder. From a psychological point of view, crime is a reaction or shortcut if the initial goal is hindered by something. In Heri's case, his main goal was to take the victim's cellphone, but when the victim found out what he had done, he used a knife as a form of pressure, committing murder as a spontaneous reaction to protect himself.